Equipment and techniques for offshore survey and site investigations - Sly, P. G. (Canadian Geotechnical Journal, 1981)
This contribution presents a recent review of equipment and field techniques applicable to offshore seabed survey work and site investigation, with particular reference to Canadian interests.During the past decade many advances have taken place in equipment design and in under standing the behaviour of mechanical sampling devices and the inadequacies of data derived from samples physically removed from the site. There has been a significant improvement in the ability of both remote and contact sensory systems to characterize and resolve differences in the physical and mechanical properties of bottom sediment materials, and the use of even simplistic remotely sensed data, if rapidly obtained and processed, offers significant economic advantages. The trend towards greater use of in situ tests will continue.The application of facies concepts, in planning field surveys, may provide opportunities for improved sample recovery, reduced sampling, and greater confidence in data interpretation.Data, comments, and examples refer to a number of Canadian situations, for example, deep ocean studies, shelf studies (such as on the Labrador Shelf, the Scotian Shelf, and the Beaufort Sea), inter-island studies in the Canadian Arctic, and inland studies in the Great Lakes and smaller lake and river systems.